Research on cryptographic technology of future network information system - Liu Xiaokai; Wang Wendong; Yang Pengfei; Yang Jiangshuai; Meng Xiangbin (Dianzi Jishu Yingyong, 2022)
This article focuses on network information cryptography technology.The strategic significance of cyberspace has become increasingly prominent. Technologies such as artificial intelligence, edge computing, and dynamic reconfiguration are widely used in cyberspace. In the future, network information systems will also face new threats and attack risks while introducing emerging technologies. This paper focuses on the characteristics of future network information system multi-domain integration, ubiquitous perception, intelligence, service customization and endogenous security, conducts security and confidentiality demand analysis and security threat and risk analysis, and designs a technology including cryptographic software and hardware platform technology, cryptography algorithms and protocols, cryptographic applications and security goals, hierarchical cryptographic architecture oriented to the future network information system.